Composite current collector, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202310637831.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-31
AI Technical Summary
[0007]上述方案所述集流体存在有耐水性能差的问题,影响电极材料与集流体的剥离性能,从而影响电极的总体效果
[0039](1)本发明所述复合集流体即具有较高的耐水性、还具有较高的导电性和安全性,制作成本低、方法简单,在不影响集流体整体导电性和与电极材料粘结性能的同时提高了集流体的耐水性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery technology, and relates to a composite current collector, its preparation method and application. Background Technology
[0002] Sodium-ion batteries have been gradually applied in consumer electronics, electric vehicles and other fields, and the market has also put forward higher requirements for sodium-ion batteries in terms of energy density, cycle life and safety.
[0003] Conductive primer technology for current collectors can effectively reduce the contact resistance between electrode materials and current collectors, increase the adhesion between them, reduce battery internal resistance, and extend battery life.
[0004] In existing technologies, aluminum foil is commonly used as the current collector material for both the positive and negative electrodes of sodium-ion batteries. For the positive electrode, the requirements for the preparation process of the nano-conductive coated aluminum current collector are the same as those for lithium-ion batteries, requiring good resistance to NMP and electrolytes. However, for the negative electrode, using the positive electrode nano-conductive coated aluminum current collector can lead to decreased adhesion and coating peeling. The main reason for this is that the negative electrode material is often water-based, while the nano-conductive coated aluminum current collector typically uses water-based binders. During the curing process, the coating forms many penetrating and non-penetrating microchannels due to water evaporation, resulting in poor water resistance. This affects the peeling performance between the negative electrode material and the current collector, thus impacting the overall electrode performance.
[0005] CN114243027A discloses a sodium-ion battery negative electrode current collector, its preparation method, and a sodium-ion battery. The sodium-ion battery negative electrode current collector includes an aluminum foil, the surface of which is an array of nanosheets.
[0006] CN217387216U discloses a negative electrode current collector, a negative electrode sheet, and a battery. The negative electrode current collector includes: an aluminum conductive layer; and a conductive functional layer. The conductive functional layer covers the surface of the aluminum conductive layer and separates the aluminum conductive layer from the electrolyte. The conductive functional layer is used to prevent ions in the electrolyte from contacting the aluminum conductive layer.
[0007] The current collector described in the above solution has poor water resistance, which affects the peeling performance between the electrode material and the current collector, thus affecting the overall performance of the electrode. Summary of the Invention
[0008] The purpose of this invention is to provide a composite current collector, its preparation method, and its application. The composite current collector of this invention has high water resistance, high conductivity, and safety. It has low manufacturing cost and simple method. While not affecting the overall conductivity of the current collector and its bonding performance with the electrode material, it improves the water resistance of the current collector.
[0009] To achieve this objective, the present invention adopts the following technical solution:
[0010] In a first aspect, the present invention provides a composite current collector, the composite current collector comprising a substrate and a conductive underlayer and a conductive water-resistant layer sequentially stacked on at least one surface of the substrate, the conductive underlayer comprising a conductive agent A, a conductive agent B and a binder, and the conductive water-resistant layer comprising a conductive agent A, a conductive agent B, a crosslinking agent and a binder.
[0011] The composite current collector of the present invention includes a conductive underlayer and a conductive water-resistant layer. The conductive water-resistant layer is located on the surface of the conductive underlayer, reducing the number of penetrating microchannels inside the coating and reducing the water penetration ability into the coating film, thereby improving the water resistance of the conductive coating without affecting the overall conductivity of the current collector or its adhesion to the electrode material.
[0012] Preferably, the substrate includes a current collector.
[0013] Preferably, the conductive agent A is a sheet-like conductive agent.
[0014] Preferably, the conductive agent A comprises conductive graphite and / or graphene.
[0015] Preferably, the particle size of the conductive agent A is 1 to 3 μm, for example: 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc.
[0016] Preferably, the conductive agent B comprises conductive carbon black and / or carbon nanotubes.
[0017] Preferably, the particle size of the conductive agent B is 200-600 nm, for example: 200 nm, 300 nm, 400 nm, 500 nm or 600 nm.
[0018] In this invention, different conductive agents A and B are added to the conductive bottom layer and the conductive water-resistant layer, respectively. Conductive agent A has a layered structure, which has good conductivity and a certain shielding effect. Conductive agent B has better ionic and electronic conductivity, has a larger specific surface area, which is conducive to the adsorption of electrolytes and thus improves ionic conductivity and rate performance.
[0019] Preferably, the crosslinking agent includes any one or a combination of at least two of isocyanates, aziridine-type curing crosslinking agents, or epoxy-type curing crosslinking agents.
[0020] Preferably, the adhesive comprises a modified polyacrylic acid adhesive and / or a polyacrylic acid adhesive.
[0021] In the conductive and water-resistant layer of the composite current collector of the present invention, the binder and crosslinking agent are mixed and heated to crosslink, which effectively improves the water resistance.
[0022] Preferably, in the conductive underlayer, the mass ratio of conductive agent B to conductive agent A is (10-20):1, for example: 10:1, 12:1, 15:1, 18:1 or 20:1, etc.
[0023] In the conductive underlayer of the present invention, the content of conductive agent B is higher than that of conductive agent A. Conductive agent B is conductive carbon black and / or carbon nanotubes, which have excellent conductivity and can take into account the conductivity of the current collector of the nano-coating.
[0024] Preferably, in the conductive underlayer, the mass ratio of conductive agent B to binder is (1-2):1, for example: 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, etc.
[0025] Preferably, in the conductive and water-resistant layer, the mass ratio of conductive agent A to conductive agent B is (10-20):1, for example: 10:1, 12:1, 15:1, 18:1 or 20:1, etc.
[0026] In the conductive and water-resistant layer of the present invention, the content of conductive agent B is lower than that of conductive agent A. Conductive agent A is a flake-shaped conductive agent with a large particle size, which has an excellent shielding effect. The addition of crosslinking agent can further enhance the water resistance of the coating.
[0027] In the composite current collector described in this invention, the conductive bottom layer has a higher proportion of nano-conductive particles (conductive agent B), resulting in superior mixing and conductivity. The conductive and water-resistant layer has a higher proportion of sheet-like micron-sized particles (conductive agent A), effectively reducing the outer layer's specific surface area and thus minimizing the formation of penetrating and non-penetrating microchannels.
[0028] Preferably, in the conductive and water-resistant layer, the mass ratio of the conductive agent A to the binder is (1-2):1, for example: 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, etc.
[0029] Preferably, in the conductive and water-resistant layer, the mass ratio of the adhesive to the crosslinking agent is (80-200):1, for example: 80:1, 100:1, 120:1, 150:1 or 200:1, etc.
[0030] Preferably, the thickness of the conductive substrate is 0.2 to 0.4 μm, for example: 0.2 μm, 0.25 μm, 0.3 μm or 0.4 μm.
[0031] Preferably, the thickness of the conductive and water-resistant layer is 0.3 to 0.8 μm, for example: 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or 0.8 μm, etc.
[0032] Preferably, the total thickness of the conductive underlayer and the conductive water-resistant layer is 0.5 to 1.2 μm, for example: 0.5 μm, 0.6 μm, 0.8 μm, 1 μm or 1.2 μm, etc.
[0033] In a second aspect, the present invention provides a method for preparing a composite current collector as described in the first aspect, the method comprising the following steps:
[0034] (1) Conductive agent A, conductive agent B and binder are mixed and dispersed to obtain a bottom conductive slurry, and conductive agent A, conductive agent B, crosslinking agent and binder are mixed and dispersed to obtain a water-resistant conductive slurry;
[0035] (2) The conductive bottom layer is coated on the substrate surface to obtain the conductive bottom layer, and the water-resistant conductive slurry is coated on the conductive bottom layer to form a conductive water-resistant layer, thereby obtaining the composite current collector.
[0036] Thirdly, the present invention provides an electrode comprising a composite current collector as described in the first aspect.
[0037] Fourthly, the present invention provides a sodium-ion battery comprising the electrode as described in the third aspect.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The composite current collector described in this invention has high water resistance, high conductivity and safety, low manufacturing cost and simple method. It improves the water resistance of the current collector without affecting the overall conductivity of the current collector and the bonding performance with the electrode material.
[0040] (2) The water droplet angle of the composite current collector described in this invention can reach more than 30°, the water content can reach less than 200ppm, exhibiting high water resistance, and the electrode resistance can reach less than 2.53mΩ. Detailed Implementation
[0041] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0042] Example 1
[0043] This embodiment provides a composite current collector, and the preparation method of the composite current collector is as follows:
[0044] (1) 10 kg of conductive carbon black with a particle size of 200 nm as conductive agent B, 1 kg of conductive graphite with a particle size of 2 μm as conductive agent A, and 40 kg of modified polyacrylic acid binder (content 25 wt%) were mixed and dispersed to obtain a bottom conductive slurry. 1 kg of conductive carbon black with a particle size of 200 nm as conductive agent B, 10 kg of conductive graphite with a particle size of 2 μm as conductive agent A, 40 kg of modified polyacrylic acid binder (content 25 wt%), and 0.08 kg of isocyanate were mixed and dispersed to obtain a water-resistant conductive slurry.
[0045] (2) A conductive bottom layer is obtained by coating a conductive bottom layer with a thickness of 12 μm on the surface of an aluminum current collector. The water-resistant conductive paste is then coated on the surface of the conductive bottom layer to obtain the composite current collector. The conductive water-resistant layer has a thickness of 0.5 μm, the conductive bottom layer has a thickness of 0.2 μm, and the total thickness of the conductive bottom layer and the conductive water-resistant layer is 0.7 μm.
[0046] Example 2
[0047] This embodiment provides a composite current collector, and the preparation method of the composite current collector is as follows:
[0048] (1) 15 kg of carbon nanotubes with a particle size of 200 nm as conductive agent B, 1 kg of graphene with a particle size of 2.2 μm as conductive agent A, and 40 kg of modified polyacrylic acid binder (content 25 wt%) were mixed and dispersed to obtain a bottom conductive slurry. 1 kg of carbon nanotubes with a particle size of 200 nm as conductive agent B, 14 kg of graphene with a particle size of 2.2 μm as conductive agent A, 40 kg of modified polyacrylic acid binder (content 25 wt%), and 0.1 kg of isocyanate were mixed and dispersed to obtain a water-resistant conductive slurry.
[0049] (2) A conductive bottom layer is obtained by coating a conductive bottom layer with a thickness of 12 μm on the surface of an aluminum current collector. The water-resistant conductive paste is then coated on the surface of the conductive bottom layer to obtain the composite current collector. The conductive water-resistant layer has a thickness of 0.5 μm, the conductive bottom layer has a thickness of 0.2 μm, and the total thickness of the conductive bottom layer and the conductive water-resistant layer is 0.7 μm.
[0050] Example 3
[0051] The only difference between this embodiment and Embodiment 1 is that the mass ratio of conductive agent A to conductive agent B in the conductive substrate is 10:1. All other conditions and parameters are exactly the same as in Embodiment 1.
[0052] Example 4
[0053] The only difference between this embodiment and Embodiment 1 is that the mass ratio of conductive agent B to conductive agent A in the conductive water-resistant layer is 10:1. All other conditions and parameters are exactly the same as in Embodiment 1.
[0054] Example 5
[0055] The only difference between this embodiment and Embodiment 1 is that the thickness of the conductive water-resistant layer is 0.2 μm; all other conditions and parameters are exactly the same as in Embodiment 1.
[0056] Example 6
[0057] The only difference between this embodiment and Embodiment 1 is that the thickness of the conductive water-resistant layer is 1 μm; all other conditions and parameters are exactly the same as in Embodiment 1.
[0058] Example 7
[0059] The only difference between this embodiment and Embodiment 1 is that the thickness of the conductive substrate is 0.1 μm; all other conditions and parameters are exactly the same as in Embodiment 1.
[0060] Example 8
[0061] The only difference between this embodiment and Embodiment 1 is that the thickness of the conductive substrate is 0.5 μm; all other conditions and parameters are exactly the same as in Embodiment 1.
[0062] Comparative Example 1
[0063] The only difference between this comparative example and Example 1 is that no conductive and water-resistant layer is provided; all other conditions and parameters are exactly the same as in Example 1.
[0064] Comparative Example 2
[0065] The only difference between this comparative example and Example 1 is that the conductive and water-resistant layer is placed in the lower layer; all other conditions and parameters are exactly the same as in Example 1.
[0066] Comparative Example 3
[0067] The only difference between this comparative example and Example 1 is that no crosslinking agent is added to the conductive and water-resistant layer; all other conditions and parameters are exactly the same as in Example 1.
[0068] Performance testing:
[0069] Water droplet angle test: The contact angles measured are the contact angles 10 seconds after the liquid (water) is dropped. Ten points are measured for each sample, and the final average value is taken.
[0070] Water content test: Under an environment of 20% relative humidity, the bottle gasket was placed in the bottle cap in advance, the solid sample was heated to 220℃, the gas flow rate was 50ml / min, the extraction time was 180s, and the relative drift value was 20μg / min.
[0071] Electrode resistance test: The solid sample was equilibrated for 72 hours under 40% humidity conditions. The penetration resistance was tested using an electrode resistance meter with a pressure of 0.3t and a holding pressure of 5s.
[0072] The test results are shown in Table 1:
[0073] Table 1
[0074] Example 1 30 193 2.53 Example 2 32 199 1.89 Example 3 32 176 5.38 Example 4 15 792 2.94 Example 5 29 272 2.34 Example 6 34 160 4.57 Example 7 33 189 2.72 Example 8 31 288 4.84 Comparative Example 1 17 756 3.03 Comparative Example 2 16 523 5.87 Comparative Example 3 25 538 2.45
[0075] As can be seen from Table 1, and from Examples 1-2, the composite current collector of the present invention has a water droplet angle of more than 30° and a water content of less than 200 ppm, exhibiting high water resistance and an electrode resistance of less than 2.53 mΩ.
[0076] Comparing Examples 1 and 3-4, it can be seen that in the conductive bottom layer of the composite current collector of the present invention, the amount of conductive agent A added is less than that of conductive agent B. Conductive agent B is conductive carbon black and / or carbon nanotubes, which have excellent conductivity and can take into account the conductivity of the nano-coated current collector. In the conductive water-resistant layer, the content of conductive agent B is lower than that of conductive agent A. Conductive agent A is a flake-shaped conductive agent with a large particle size, which has excellent shielding effect. The addition of crosslinking agent can further enhance the water resistance of the coating.
[0077] A comparison of Examples 1 and 5-6 shows that the thickness of the conductive and water-resistant layer in the composite current collector of the present invention affects its performance. When the thickness of the conductive and water-resistant layer is controlled between 0.3 and 0.8 μm, the composite current collector has better performance. If the thickness of the conductive and water-resistant layer is too large, the conductivity deteriorates; if the thickness of the conductive and water-resistant layer is too small, the water resistance deteriorates.
[0078] A comparison of Examples 1 and 7-8 shows that the thickness of the conductive substrate in the composite current collector of the present invention affects its performance. When the thickness of the conductive substrate is controlled between 0.2 and 0.4 μm, the composite current collector has better performance. If the thickness of the conductive substrate is too large, the water resistance will deteriorate, and the conductivity will also decrease. If the thickness of the conductive substrate is too small, the conductivity will also be affected due to the reduced conductive content of the substrate.
[0079] As can be seen from the comparison between Example 1 and Comparative Examples 1-2, the conductive water-resistant layer of the present invention is located on the surface of the conductive bottom layer, which reduces the number of penetrating microchannels inside the coating and reduces the water penetration ability into the coating film, thereby improving the water resistance of the nano-conductive coating without affecting the overall conductivity of the current collector or its adhesion to the electrode material.
[0080] As can be seen from the comparison between Example 1 and Comparative Example 3, the addition of a crosslinking agent to the conductive water-resistant layer of the present invention can further enhance the water resistance of the coating.
[0081] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A composite current collector, characterized in that, The composite current collector includes a substrate and a conductive underlayer and a conductive water-resistant layer sequentially stacked on at least one surface of the substrate. The conductive underlayer includes a conductive agent A, a conductive agent B, and a binder. The conductive water-resistant layer includes a conductive agent A, a conductive agent B, a crosslinking agent, and a binder. The conductive agent A is a sheet-like conductive agent, and the conductive agent B includes conductive carbon black and / or carbon nanotubes. In the conductive bottom layer, the mass ratio of conductive agent B to conductive agent A is (10~20):1, and in the conductive water-resistant layer, the mass ratio of conductive agent A to conductive agent B is (10~20):
1.
2. The composite current collector as described in claim 1, characterized in that, The substrate includes a current collector.
3. The composite current collector as described in claim 1, characterized in that, The conductive agent A includes conductive graphite and / or graphene.
4. The composite current collector as described in claim 1, characterized in that, The conductive agent A has a particle size of 1~3μm.
5. The composite current collector as described in claim 1, characterized in that, The particle size of the conductive agent B is 200~600nm.
6. The composite current collector as described in claim 1, characterized in that, The crosslinking agent includes any one or a combination of at least two of isocyanates, aziridine-type curing crosslinking agents, or epoxy-type curing crosslinking agents.
7. The composite current collector as described in claim 1, characterized in that, The adhesive includes modified polyacrylic acid adhesive and / or polyacrylic acid adhesive.
8. The composite current collector as described in claim 1, characterized in that, In the conductive substrate, the mass ratio of the conductive agent B to the binder is (1~2):
1.
9. The composite current collector as described in claim 1, characterized in that, In the conductive and water-resistant layer, the mass ratio of the conductive agent A to the binder is (1~2):
1.
10. The composite current collector as described in claim 1, characterized in that, In the conductive and water-resistant layer, the mass ratio of the adhesive to the crosslinking agent is (80~200):
1.
11. The composite current collector as described in claim 1, characterized in that, The thickness of the conductive substrate is 0.2~0.4μm.
12. The composite current collector as described in claim 1, characterized in that, The thickness of the conductive and water-resistant layer is 0.3~0.8μm.
13. The composite current collector as described in claim 1, characterized in that, The total thickness of the conductive underlayer and the conductive water-resistant layer is 0.5~1.2μm.
14. A method for preparing a composite current collector as described in any one of claims 1-13, characterized in that, The preparation method includes the following steps: (1) Conductive agent A, conductive agent B and binder are mixed and dispersed to obtain a bottom conductive slurry, and conductive agent A, conductive agent B, crosslinking agent and binder are mixed and dispersed to obtain a water-resistant conductive slurry; (2) The conductive bottom layer is coated on the substrate surface to obtain the conductive bottom layer, and the water-resistant conductive slurry is coated on the conductive bottom layer to form a conductive water-resistant layer, thereby obtaining the composite current collector.
15. An electrode sheet, characterized in that, The electrode comprises a composite current collector as described in any one of claims 1-13.
16. A sodium-ion battery, characterized in that, The sodium-ion battery comprises the electrode as described in claim 15.
Citation Information
Patent Citations
Negative current collector, negative plate and battery
CN217387216U
Dual-layer method of fabricating ultracapacitor current collectors
CN103098161A
Composite current collector resistant to corrosion and high in electroconductivity and manufacturing method thereof
CN104465126A
Negative electrode current collector and negative electrode
CN114843520A